Comparison of low calorie high protein and low calorie standard protein diet on waist circumference of adults with visceral obesity and weight cycling - Fiastuti Witjaksono (BMC Research Notes, 2018)
Abstract Objectives Many individuals with visceral obesity who previously had succeeded in reducing body weight regain and this loss–gain cycle repeats several times which is called as weight cycling. We aimed to evaluate the effect of a low calorie high protein diet (HP) compared to a low calorie standard protein diet (SP) on waist circumference of visceral obese adults with history of weight cycling. Results In this open-randomized clinical trial, participants were asked to follow dietary plan with reduction in daily caloric intake ranging from 500 to 1000 kcal from usual daily amount with minimum daily amount of 1000 kcal for 8 weeks and were divided in two groups: HP group with protein as 22–30% total calorie intake; and SP group with protein as 12–20% total calorie intake. There was a statistically significant difference (P < 0.001) between waist circumference before and after the dietary intervention among both groups. Meanwhile, there was no statistically significant difference in the mean reduction of waist circumference between HP and SP groups (P = 0.073). Taken together, the protein proportion does not significantly affected waist circumference. Trial registration ClinicalTrials.gov NCT03374150, 11 December 2017